Rancang Bangun Inverter Mini 1.5 Vdc to 220 Vac Untuk Lampu Darurat - Syahrir Abdussamad (Universitas Negeri Gorontalo, 2020)
Used cellphone charger components are used as an alternative to create emergency lights which can later be used by the community when the power source from the grid goes out. The purpose of this study is to utilize the components of a used cellphone charger which is the Joule Thief transformer to create 1.5 Vdc to 220V ac mini inverter. The method used in this study is the experimental method, which starts from the selection of tools and materials to measuring the outputs. The results showed that the design of a 1.5 Vdc to 220 Vac mini inverter with Joule Thief can turn on 220 Vac LED lights without drivers. Tests were carried out on 1 watt driverless 220 Vac LED lights. Experiments were carried out to test the dc source durability in the form of 1.5 Vac battery. From testing for LED lights 1, 2 and 3 it turns out that the current and voltage gradually decreased due to the use of LED lights. The resources quickly ran out when the inverter was used for 3 LED lights. The design of tools can be used as an emergency light when the source of electricity from the grid.